Novel 3-substituted fluorine imidazolium/triazolium salt derivatives: synthesis and antitumor activity1. Issue 78 (26th August 2015) - Liu, Jin-Mei; Wang, Min; Zhou, Yun-Jing; Yan, Ju-Ming; Yang, Li-Juan; Li, Yan; Zhang, Hong-Bin; Yang, Xiao-Dong
<x xml:space="preserve">Abstract</x> A series of novel (±)-3-substituted fluorene–imidazolium/triazolium salt derivatives were synthesized and their antitumor structure–activity relationship studies were reported.